PENINGKATAN FUNGSI KESEHATAN LANSIA MELALUI PEMBEKALAN SIGAP OBAT (SIAP GUNAKAN DAN ANTISIPASI PEMAKAIAN OBAT) PADA SELANTANG - Lindawati Setyaningrum (Jurnal SADEWA, 2025)
Elderly individuals often experience difficulty in medication management, which has the potential to reduce their quality of life. Monitoring drug use and anticipating potential risks is very important in maintaining the healthy function of the elderly. Therefore, health promotion education regarding the "use and anticipation of risks" of effective medication aims to increase public awareness and prevent health problems resulting from drug abuse. The methods used include Group Counseling, Practical Demonstration, and One-on-One Approach. Results achieved include increased understanding, awareness of the risks associated with drug use, and changes in drug use behavior. By applying these various methods, education about the appropriate use of drugs and the potential risks of using drugs has succeeded in increasing public knowledge and awareness regarding how to use drugs safely and can increase patient compliance with treatment, and ultimately improve people's quality of life.